Adaptation and evaluation of the Chinese hospital nursing department disaster preparedness scale: a cross-sectional scale development study. Issue 4 (1st April 2021) - Shi, Lan; Li, Mingxuan; Xu, Xiaofeng; Wang, Zhengdong; Li, Sijian; Feng, Xianqiong
Abstract : Aim: The aim of this study was to adapt the Chinese version of Hospital Nursing Department Disaster Preparedness Scale (HNDDPS) and evaluate the psychometric properties among hospital nurses in China. Two specific objectives were (1) to adapt the HNDDPS from Sadiq's Organisational Disaster Preparedness Scale (SODPS) to fit the context of Chinese hospital nursing system and (2) to establish its validity and reliability. Design: Instrument design study. Settings and participants: 2657 nurses belonging to 50 nursing organisations of tertiary hospitals spread across seven administrative regions of China. Methods: We adapted the Chinese version of HNDDPS through translation of the SODPS, back translation and cultural adaptation. Subsequently, we evaluated the validity of the scale through exploratory factor analysis and confirmatory factor analysis (CFA), each performed on half of the original sample. We also evaluated the internal consistency reliability of the scale. Results: The Chinese version of HNDDPS comprised five dimensions, with 72 items. Exploratory factor analysis yielded five factors explaining 61% of the items' variance. CFA confirmed five dimensions of the scale and produced appropriate Goodness of Fit Indexes. Cronbach's α-coefficient was 0.930 for the total scale and ranged from 0.908 to 0.964 for the five dimensions of the scale. Conclusion: HNDDPS demonstrates good internal consistency and construct validity. It is a promising, valid and reliable tool for nurses and nursing managers to evaluate hospital nursing department disaster preparedness.